The Effect of Problem-Based Learning Model on Learning Motivation and Its Impact on Students' Learning Achievement - Idkhan, A. Muhammad; Irfan, Andi Muhammad; Putra, Iswahyudi Indra; Romadin, Achmad (International Journal of Integrative Sciences, 2024)
To evaluate the effectiveness of the problem-based learning (PBL) model on learning motivation and its impact on the academic achievement of PTM FT UNM students, a study will be conducted. This research will use a quantitative approach with path analysis. Path analysis is a statistical method that provides a quantitative interpretation for multiple variables within an analysis model. It tests the influence between independent and dependent variables by analyzing both direct and indirect effects among the variables. Regression correlation analysis will be employed to determine the percentage contribution of the independent variable to the dependent variable. The data processing results indicate that the PBL model and learning motivation together affect learning achievement by 13.8%, while the remaining 86.2% is influenced by other factors. Specifically, the PBL model accounts for 7.00% of the effect on achievement, with 93.00% attributed to other unexamined factors. Additionally, the PBL model impacts motivation by 28.65%, with the remaining 71.35% influenced by other factors not studied